MENGINTEGRASIKAN PENDIDIKAN SAINS DAN EKONOMI KEUANGAN UNTUK MENINGKATKAN KEWIRAUSAHAAN BERBASIS PENGETAHUAN - Muhammad Nadhar; Norhaedah Norhaedah; Sariana Sariana; Ernawati Ernawati; Syamsuni Syamsuni HR (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the integration of science and financial economics education in higher education curricula to foster knowledge-based entrepreneurship in the context of globalization and digitalization. Using a qualitative approach with literature analysis and focus group discussions (FGDs) involving academics and business practitioners, the research highlights how a multidisciplinary approach—merging scientific knowledge and financial economics—can enhance entrepreneurial skills. This integration not only deepens theoretical understanding but also equips students with essential financial skills for sustainable business practices. The study underscores the need for educational policies that promote synergy between these fields to cultivate competitive, knowledge-driven entrepreneurs in the futuree.